2021
DOI: 10.1016/j.isci.2021.102375
|View full text |Cite
|
Sign up to set email alerts
|

Biased perceptions explain collective action deadlocks and suggest new mechanisms to prompt cooperation

Abstract: Summary When individuals face collective action problems, their expectations about others' willingness to contribute affect their motivation to cooperate. Individuals, however, often misperceive the cooperation levels in a population. In the context of climate action, people underestimate the pro-climate positions of others. Designing incentives to enable cooperation and a sustainable future must thereby consider how social perception biases affect collective action. We propose a theoretical model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Thirdly, noise in the perceptions of agents can affect cooperation in learning and evolutionary dynamics 70 . For example, inaccurate observations can lead to better learning outcomes in faster learning time, the stabilization of an otherwise chaotic learning process, and the mitigation of social dilemmas 71 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, noise in the perceptions of agents can affect cooperation in learning and evolutionary dynamics 70 . For example, inaccurate observations can lead to better learning outcomes in faster learning time, the stabilization of an otherwise chaotic learning process, and the mitigation of social dilemmas 71 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In general, exploration of social norming interventions is important because false beliefs that deviate from a social consensus are not only potential drivers of misinformed and thus potentially harmful behaviours (e.g., Bauman & Geher, 2002;Botvin, Botvin, Baker, Dusenbury, & Goldberg, 1992), but they can also affect public discourse. Specifically, overestimation of the social acceptance of one's view (i.e., a false-consensus effect; Marks & Miller, 1987) can be detrimental if the view is ill-informed: For example, a person assuming that many others share the misconception that anthropogenic climate change is a hoax will be motivated to promote their false view and actively oppose mitigative action (e.g., Santos, Levin, & Vasconcelos, 2021). On the flipside, if a vocal minority keeps a false belief in the public spotlight, this can lead people who hold a factual majority belief to underestimate the social acceptance of their view and falsely assume they are in the minority (i.e., a false-uniqueness effect; Bosveld, Koomen, van der Pligt, Plaisier, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Social biases may be particularly problematic for collective action problems like climate change or vaccination, where a minimal threshold of cooperation is required. In simulations of public goods games, Santos and colleagues (2021) observe that underestimating others’ cooperative intentions is particularly detrimental to collective action because it requires a high number of default cooperators to avoid deadlock. They also found that a tendency to perceive others’ attitudes as deviating from one’s own can further undermine cooperation intentions.…”
Section: Misperceiving Others’ Perspectives As a Threat To Sciencementioning
confidence: 99%